Síndrome de Burnout en Trabajadores de Una Industria del Sector Metalmecanico en Bogota (2013)
In the last few years have been made several investigations of the Burnout syndrome in the area of health care services and that “understood as a set of signs and symptoms that appear as a result of a lower reward than expected on the part of the work done”. This research is conducting a study on the burnout dimensions that comprise the behavioral symptoms, physical and emotional, in the staff working in an industrial company. It is a quantitative, descriptive and exploratory study of 52 workers from a manufacturing and industrial marketing company of the Bogota city.